2012
DOI: 10.1007/s00404-012-2265-y
|View full text |Cite
|
Sign up to set email alerts
|

Spinal versus general anesthesia in cesarean sections: the effects on postoperative pain perception

Abstract: Spinal anesthesia is comparable to general anesthesia in terms of post-operative pain control. In choosing the type of anesthesia in CS, other factors such as the urgency and potential maternal and fetal hazards should be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 25 publications
1
23
0
1
Order By: Relevance
“…No studies are available that investigate how these anesthesia techniques affect postoperative pain when applied to both emergent and elective cesarean sections. In the present study, postoperative pain was evaluated in four groups, [6]. In the first postoperative 8 h, they found that VAS scores were significantly higher in patients with spinal anesthesia compared to patients administered general anesthesia (3.9 versus 3.2, respectively) [6].…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…No studies are available that investigate how these anesthesia techniques affect postoperative pain when applied to both emergent and elective cesarean sections. In the present study, postoperative pain was evaluated in four groups, [6]. In the first postoperative 8 h, they found that VAS scores were significantly higher in patients with spinal anesthesia compared to patients administered general anesthesia (3.9 versus 3.2, respectively) [6].…”
Section: Discussionmentioning
confidence: 61%
“…In the present study, postoperative pain was evaluated in four groups, [6]. In the first postoperative 8 h, they found that VAS scores were significantly higher in patients with spinal anesthesia compared to patients administered general anesthesia (3.9 versus 3.2, respectively) [6]. The authors emphasized that these scores were within low to moderate ranges in defining pain intensity and had negligible clinical significance.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Hasil analisis menunjukkan tidak ada perbedaan intensitas nyeri pada berbagai posisi pada kedua kelompok penggunaan anestesi ini. Hasil penelitian ini mendukung hasil penelitian sebelumnya yang menunjukkan skor nyeri pada kedua kelompok hampir seimbang, sehingga tidak terdapat perbedaan intensitas nyeri pada 6 sampai dengan 24 jam paska operasi (Kessous et al, 2012;Naghibi, Saryazdi, Kashefi & Rohani, 2013).…”
Section: Pembahasanunclassified
“…Certain diseases causing bleeding tendencies may also preclude the use of a regional anesthesia. In addition, general anesthesia is a requirement when a regional anesthesia is not successful to provide the proper amount of anesthesia necessary to perform cesarean operation [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%